Direct design to horizontal sway, limitation for unbraced steel frames - Saim, A. Aziz (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1999)
A meth od applicable to the design of unbraced multi-storey steel frames to specified limits on horizontal sway deflection is presented. This method of design is the extension and combination of the work by Wood and Roberts ell and Anderson and Islam [2]. Only simple calculations are required by the method and its application is illustrated by worked examples. Regular and nonregular steel frames are considered. The method proposed is suitable for the design of unbraced multi-storey frames if the choice of sections is contro lled by sway de flection.